Simulating systems of systems using situation/reaction paradigm. (30th August 2018) - Benabidallah, Rymel; Sadou, Salah; Esnault, Armel; Nacer, Mohamed Ahmed
Summary: Modeling and simulation play a major role in complex system engineering. In Systems of Systems (SoS) engineering, a special case of complex systems engineering, they help to better understand and identify the side effects associated with the integration of autonomous constituent systems. Simulation is also a way of apprehending the emerging behaviors from this integration. The dynamic and evolving nature of the SoS environment has led us to rely on their most stable part to define them, namely their mission. In this paper, we propose a simulation framework for SoS based on a mission conceptual model. Mission is defined as a set of situations that require reactions. Situations are defined by rules on facts related to the SoS environment. Reactions are defined as orchestrations of services from constituent systems (subsystems) that must be triggered when a situation is identified. We present this simulation approach through a case study on a Telediabet SoS.